GATE convection subprogramme: field phase report - Betts, A. K., author; Rodenhuis, D. R., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1975)
A summary of the in-field decisions affecting the GATE Convection Subprogramme (C.S.P.) objectives

a preliminary tabulation and discussion of the data collection

and a discussion of the work of the Special Analysis Group in Dakar. Preliminary tables are presented of the upper air data coverage for the B and A/B ship arrays, the C-band ship radars, the SMS satellite coverage and the multi-aircraft missions flown in support of the C.S.P.A preliminary assessment of the subprogramme observational objectives is given.
Assisted by J. L. Rasmussen and W. Murray of the U.S. GATE Project Office.
February, 1975.
Keywords: Convection (Meteorology)